Probiotic containing Lactobacillus casei, Lactobacillus bulgaricus, and Streptococcus thermophiles (ACTIMEL) for the prevention of Clostridium difficile associated diarrhoea in the elderly with proximal femur fractures - Ravi Mallina, MD; J. Craik, FRCS; N. Briffa, FRCS; Viren Ahluwalia, BSc, MBChB; J. Clarke, FRCP; A.G. Cobb, FRCS (Elsevier, 2018)
The incidence of Clostridium difficile associated diarrhoea (CDAD) is greater in elderly patients. Probiotics may have a beneficial effect in the prevention of CDAD. However, their effect in elderly orthopaedic patients has not been previously reported. Between April 2013 and April 2014, 105 patients admitted with femoral neck fractures, and who required 3 days of antibiotics for infection of any cause, were prescribed the probiotic ACTIMEL until 3 days after the last antibiotic dose. The incidence of CDAD was compared with historical controls (April 2011￢ﾀﾓApril 2012). There was no significant reduction in the incidence of CDAD in patients receiving probiotics (OR: 0.9; 95% CI 0.27￢ﾀﾓ2.91; p = 0.8) and therefore we cannot recommend the use of ACTIMEL containing Lactobacillus casei, Lactobacillus bulgaricus, and Streptococcus thermophiles for this purpose in this patient group. Keywords: Clostridium difficile￢ﾀﾔassociated diarrhoea, Probiotics, Antibiotics